Small-scale cheese manufacture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
'Traditional Cheesemaking', by Josef Dubach, published by Intermediate Technology 74pp, ISBN 0-946688 43 5